Evaluating the Effectiveness of Policies and Status of People with Disabilities in Oman - Mishrif, Ashraf (British Journal of Healthcare and Medical Research, 2025)
The need for regulating and managing the activities of people with disabilities requires clear and effective policy measures that guarantee the rights and protect the interests of this group of people. Developed and developing countries alike designed and introduced various forms of policy measures and procedures to improve the quality of life of people with disabilities, but the implementation and development of these measures appear to be considerably weak and slow in most developing countries, where most people with disabilities are deprived of their basic rights. This argument is validated through a comprehensive investigation of the current policies, procedures, and programmes that support people with disabilities to become entrepreneurs. The perceptions of people with disability toward the current procedures and policies in terms of empowering them in various entrepreneurial aspects are assessed through focused group discussions with government officials at the Directorate General for Disabled Affairs, Ministry of Social Development, and disabled entrepreneurs who are categorized as self-employed in the Sultanate of Oman. The results reveal that disabled entrepreneurs consider the current entrepreneurial policies as fragmented and ineffective, hence urging the government to modify the current policies to meet the requirements of people with disability in establishing and running their own enterprises.